Origin of Fungicide Resistant Barley Powdery Mildew in Western Australia: Lessons to be learned - Tucker, Madeline; Lopez-Ruiz, F.; Jayasena, Kithsiri; Oliver, Richard (Springer, 2015)
The risk of fungicide resistance is greatest with pathogens with short dormant periods, with both sexual and asexual reproduction cycles, with large population sizes and when fungicides of a single mode of action (MOA) are repeatedly used. Most of the barley growing area in Western Australia (WA) has been seeded with powdery mildew (Blumeria graminis f. sp. hordei (Bgh)) susceptible cultivars for the last 10–15 years. Fungicides from the triazole group dominate the market and are used repeatedly as both seed and foliar treatments. Field failures have been observed leading to losses estimated at AU$100 m annually since 2007. Reduced efficacy has often been found to result from alterations in the gene encoding triazole target 14α-sterol demethylase (CYP51 syn. ERG11). Clear associations were found between accumulations of CYP51 mutations and reductions in triazole sensitivity. The combination of susceptible cultivars, conducive environmental conditions and repeated use of a single MOA has led with disappointing predictability to perhaps the most costly fungicide resistance epidemic in history.